Chlorine efficacy against bacteriophage Phi6, a surrogate for enveloped human viruses, on porous and non-porous surfaces at varying temperatures and humidity. Issue 8 (3rd July 2022) - String, Gabrielle M.; Kamal, Yarmina; Gute, David M.; Lantagne, Daniele S.
Abstract: While efficacy of chlorine against Phi6, a widely-used surrogate for pathogenic enveloped viruses, is well-documented, surfaces common to low-resource contexts are under-researched. We evaluated seven surfaces (stainless steel, plastic, nitrile, tarp, cloth, concrete, wood) and three environmental conditions—temperature (4, 25, 40 °C), relative humidity (RH) (23, 85%), and soiling—to determine Phi6 recoverability and the efficacy of disinfection with 0.5% NaOCl. Overall, Phi6 recovery was >4 log10 PFU/mL on most surfaces after drying 1 hour at all temperature/humidity conditions. After disinfection, all non-porous test conditions (48/48) achieved ≥4 LRV at 1 and 5 minutes of exposure; significantly more non-porous surfaces met ≥4 LRV than porous ( p  < 0.001). Comparing porous surfaces, significantly fewer wood samples met ≥4 LRV than cloth ( p  < 0.001); no differences were observed between concrete and either wood ( p  = 0.083) or cloth ( p  = 0.087). Lastly, no differences were observed between soil and no-soil conditions for all surfaces ( p  = 0.712). This study highlights infectious Phi6 is recoverable across a range of surfaces and environmental conditions, and confirms the efficacy of chlorine disinfection. We recommend treating all surfaces with suspect contamination as potentially infectious, and disinfecting with 0.5% NaOCl for the minimum contact time required for the target enveloped virus (e.g. Ebola, SARS-CoV-2).